ANALYSIS OF STUDENTS’ MATHEMATICAL CRITICAL THINKING ABILITY REVIEWED IN SOLVING MATHEMATICS PROBLEMS FROM GENDER DIFFERENCES - Sugiarti, Lana; Tamur, Maximus; Jehadus, Emilianus; Jundu, Ricardus; Limur, Matilda (Program Studi Pendidikan Matematika FKIP Universitas Pattimura, 2023)
This study aims to determine students' mathematical critical thinking skills in terms of gender differences. This research was conducted in March 2023 in class VII junior high school. The subjects of this study consisted of 6 people, including 3 male students and 3 female students. Based on the gender of each student, they are then grouped into 2 people with high ability categories, 2 people with medium ability categories, and 2 people with low ability categories. This type of research is a descriptive research. Data collection techniques were carried out using a written test consisting of 2 questions, by interview and documentation. Data analysis techniques consist of three stages, namely data is data reduction, data presentation, and drawing conclusions. Test the validity of the data using method triangulation techniques and data source triangulation. The results showed that students with high abilities could work on critical thinking test questions and covered all the indicators. In contrast, students with moderate abilities still needed to be able to work on mathematical critical thinking test questions well according to the criteria for critical mathematical thinking. Students with low abilities have yet to be able to do well on the mathematical critical thinking test according to the criteria of critical mathematical thinking. No significant difference exists between how to solve the test questions for male and female students in each ability category